The TUITEK® patient support program improved caregiver-related behaviors on growth hormone treatment adherence - Ekaterina Koledova; Pen-Hua Su; Pen-Hua Su; Yen-Ju Chen; Aria Assefi; Matias Debicki; Debbie Cooke; Amrit Jheeta; Alexander B. Jones; Jung Eun Moon (Frontiers in Endocrinology)
BackgroundRecombinant human growth hormone (r-hGH) can improve or normalize growth outcomes in pediatric patients with growth hormone deficiency, but poor adherence to the treatment regimen limits treatment effectiveness. TUITEK® is a multicomponent patient support program (PSP) designed to deliver support aimed at behavior change that is personalized to the needs of individual caregivers and patients throughout the treatment care pathway. The aim was to assess the impact of the TUITEK® PSP on knowledge, beliefs and perceptions of adherence to r-hGH treatment in high-risk caregivers.Patients and methodsA prospective pre–post research was conducted across the combined population of caregivers of patients with short stature receiving r-hGH treatment in the TUITEK® PSP in Argentina, South Korea, and Taiwan. Caregivers who were categorized as high-risk based on suboptimal knowledge, beliefs and perceptions of factors influencing adherence to r-hGH treatment (disease and treatment coherence, emotional burden, self-administration, and treatment-related anxiety) were included in the analysis.ResultsIn total, data from 409 caregivers were available. Involvement in the TUITEK® PSP resulted in a statistically significant (p<0.0001) positive change for all factors. Improvements were reflected in the number of caregivers who moved from high- to low-risk at the end of the TUITEK® PSP. The overall changes were reflected in the changes observed when data were analyzed for individual countries separately.ConclusionsThe TUITEK® PSP successfully improved key caregiver-related behaviors that may negatively impact adherence to r-hGH treatment and might improve adherence and therefore clinical outcomes.